Can parked cars and carbon taxes create a profit? The economics of vehicle-to-grid energy storage for peak reduction. (July 2017) - Freeman, Gerad M.; Drennen, Thomas E.; White, Andrew D.
Abstract: This article discusses a five-year, hourly economic model of vehicle-to-grid energy storage for peak reduction. Several scenarios are modeled for a participant using a 60 kW-h capacity battery electric vehicle, such as the Tesla Model S or Chevrolet Bolt, in the New York City area using pricing data for the years 2010 through 2014. Sensitivity analysis identifies that variables such as one-way power efficiency and battery lifetime are the major factors influencing the economics of selling electricity back to the grid. Although it is shown that vehicle-to-grid electricity sales can create positive economic benefits, the magnitudes are small due to the cost of added degradation to the vehicle's battery and are not likely to entice the average electric vehicle owner to participate. However, over the five-year period, the potential economic benefits of this technology have shown a promising trend. A carbon dioxide tax is examined as a potential policy measure to encourage vehicle-to-grid adoption. The implementation of a carbon dioxide tax is shown to create additional opportunities for economic gain but, these benefits are dependent on the grid's electricity generation portfolio. Added benefits from the tax are also small in magnitude considering current international carbon prices. Highlights: Three scenarios of vehicle-to-grid storage for peak reduction are proposed. Average annual savings generated by vehicle-to-grid are small but positive. Savings have remained positive or increased during 2010–2014. Moderate carbon tax policies can generate extra savings, but they are small.